# Chapter 2 Pre Test. 1. x – 9 = - 12 +9 x = - 3 +9 Step 5.

## Presentation on theme: "Chapter 2 Pre Test. 1. x – 9 = - 12 +9 x = - 3 +9 Step 5."— Presentation transcript:

Chapter 2 Pre Test

1. x – 9 = - 12 +9 x = - 3 +9 Step 5

x = 6 - 3 - 3x = - 18 - 3 2. Step 6 Step 7

( ) x = 15 5 1 x = 75 5 ( ) 5 3. Step 2

3 3x – 9 = 6 3 x = 5 3x = 15 +9 +9 4. Step 5Step 6 Step 7

2 7x – 3 = 5x + 11 2 x = 7 2x = 14 +3 +3 -5x -5x 5. Step 4 Step 5Step 6 Step 7

2 7x + 1 – 5x + 3 = 12 2 x = 4 2x = 8 -4 -4 2x = 12 + 4 6. Step 3 Step 5Step 6 Step 7

7. 2.3x – 3.7 = 2.9x – 7.3 - 6 2.3x – 3.7 = 2.9x – 7.3 - 6 x = 6 - 6x = - 36 +37+37 -29x -29x 10( )10( )10( )10( ) 23x – 37 = 29x – 73 Step 2 Step 4 Step 5Step 6 Step 7

10 2(4x – 5) – 6 = 8 – 2(x – 8) 10 10x = 40 +16 +16 +2x +2x 8x 8x – 16 x = 4 = 24 – 2x – 10 = 8– 2x – 6 + 16 8. Step 1 Step 3 Step 4Step 5 Step 6 Step 7

Step 5Step 6 Step 7 -3 12 4 1 9. x + = x ( ) 12 4 4 3 4x -3 -8x -8x x = 3 ( ) - 4 - 4 - 4x = - 12 LCD = 12 3 1 4 1 3 2 4 3 – 3 x 3 2x 4 3 – = + 3 + 3=8x – 9 Step 2 Step 4

- 1 -2x – ( ) 10. = ( ) 4 4 1 1 2 x + 1 -1 -1 -2x x = 3 4 1 – ( ) 4 - 1 - x = - 3 (x + 1) x 2 1 2 1 = 4 x + 2 x 4 1 2 1 4 2 LCD = 4 = 2x – 2 Step 1 Step 2 Step 4Step 5 Step 6 Step 7

12 4 1 11. x – + = x 12 4 6 4x -3 -3 -12x -12x - 8 - 8 - 8x = - 3 LCD = 12 3 1 4 1 2 1 3 x 2 1 = + – 3 – 3+ 6 = 12x x 4x + 3 = 12x x =  ( ) Step 2 Step 3 Step 4Step 5 Step 6 Step 7

12. = 5 ( ) 3 3 1 x – 6 +6 +6 x = 21 3 1 ( ) 3 (x – 6) = 3 x – 5 LCD = 3 = 15 Step 1 Step 3 Step 5 2

13.Solve for y. - 5 4x – 5y = 10 - 5 - 5y = - 4x + 10 -4x -4x y = - 4x + 10 -5-5 -5-5 y = – 2 4 5 x Step 4 Step 6 Step 7

5 4 (5) 14. Go back to question and answer 13 and find y when x = 5. y = 4 – 2 y = 2 y = – 2 4 5 x 1

15.Solve for d π C = πd π d = C π Step 6

16.Go back to question and answer 15 and find d when C = 314 and π = 3.14 d = C π 314 3.14 d = 100

Chapter 2 Pre Test

Download ppt "Chapter 2 Pre Test. 1. x – 9 = - 12 +9 x = - 3 +9 Step 5."

Similar presentations